Post Corporate Restructuring Analysis: The Case of Malaysian Resources Corporation Berhad (MRCB) - Ainulashikin Marzuki; Nur Ainna Ramli; Fauzias Mat Nor; Norazlan Alias; Mohd Hasimi Yaacob (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA